THE EFFECT OF ROLE PLAY LEARNING METHOD TO STUDENT'S ACHIEVEMENT IN PHOTOSYNTHESIS TOPIC - Juarsa, Muhamad Isha (2014)
The achievement of Indonesian students about biology is relatively low. It could be seen from PISA 2009 study result which shows that Indonesia's score was decrease into 383 and become the 60th out of 65 participants. This study aims to examine the effect of role play learning method to student's achievement in photosynthesis topic. The type of this study was weak experiment with one group pretest and postest design. Population in this research was grade 8 of junior high school students at one of the school in Bandung. The achievement test data was taken by pre test and post test, meanwhile the non test data gathered through observation sheet, questionnaire, and student's multiple intelligence analysis. Based on the analysis of the result, the observation sheet shows that the implementation was representative. This research obtained improvement in the achievement with normalized gain 0,41 which was categorized into medium improvement. Based on the result of questionnaires, the implementation of role play can increase student's interest, activeness, understanding, as well as student's communication. Role play also can trigger students to collaborate in their groups. Beside that role play can make students think more contextual. Moreover, role play was considered as new and innovative method by students. Role play generally can improve students achievement in any type of intelligence. Beside that in group composition, role play method do not need specific type of intelligence to be in the same group